1989
DOI: 10.1037/0033-2909.106.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in positive well-being: A consideration of emotional style and marital status.

Abstract: This article reviews all published studies reporting tests for sex differences in well-being. Women were found to report greater happiness and life satisfaction than men. This sex difference was explained in terms of men's and women's social roles: The female (vs. male) gender role specifies greater emotional responsiveness. Furthermore, past role-related experiences provide women with appropriate skills and attitudes. Women's (vs. men's) greater well-being was also found to hold for married but not unmarried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
173
1
17

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(210 citation statements)
references
References 167 publications
16
173
1
17
Order By: Relevance
“…Literature review showed that there were different results concerning the relationship between subjective well-being and gender. For instance, Haring et al (1984) conducted a meta-analysis of 146 studies and found that males were slightly tend to be more happy than females, but this difference was very small; while Wood et al (1989), in a metaanalysis of 93 studies, concluded that females were more happy than males. Similarly, Shmotkin (1990) stated that, when all other variables are controlled, females expressed higher subjective well-being when compared to males.…”
Section: Resultsmentioning
confidence: 99%
“…Literature review showed that there were different results concerning the relationship between subjective well-being and gender. For instance, Haring et al (1984) conducted a meta-analysis of 146 studies and found that males were slightly tend to be more happy than females, but this difference was very small; while Wood et al (1989), in a metaanalysis of 93 studies, concluded that females were more happy than males. Similarly, Shmotkin (1990) stated that, when all other variables are controlled, females expressed higher subjective well-being when compared to males.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in an international comparative study involving analysis of data from 41 countries, Haller and Hadler (2006) found that women scored significantly higher both on life satisfaction and overall happiness; whereas in an extensive meta-analytic review of 93 studies, Haring, Stock, and Okun (1984) reported a slight tendency for men to report higher levels of happiness. However, clearer gender differences have been found in affect with women reporting higher levels of PA and NA than men (Nolen-Hoeksema & Rusting, 1999;Wood et al, 1989).…”
Section: Gender Differences In Swbmentioning
confidence: 99%
“…Wood and her colleagues (Wood, Rhodes, & Whelan, 1989;Wood & Rhodes, 1992;Grossman & Wood, 1993) argued that gender differences in mood and behaviors come mainly from socially-prescribed gender roles. The content of social stereotyping "obligates" women to be more expressive of emotions, especially sadness and fear, more concerned with their own and other's emotional states, and more emotionally labile than men (Grossman & Wood, 1993;Brody & Hall, 1993).…”
Section: Gender Differences In Swbmentioning
confidence: 99%
“…Empirical studies report, life satisfaction is related to age [2,4,9,12,13,15,19,28,52,63], gender [5,6,56,61], marital status [16,34,51,56,60], and household size [34]. With regard to socio-economic status and life satisfaction, while some studies report a negative [10,20,21,22,26,27,40], others suggest a positive [11,29,30,33,34] relationship.…”
Section: Exogenous Conceptsmentioning
confidence: 99%